Mortality among US veterans after emergency visits to Veterans Affairs and other hospitals: retrospective cohort study. (16th February 2022) - Chan, David C; Danesh, Kaveh; Costantini, Sydney; Card, David; Taylor, Lowell; Studdert, David M
Abstract: Objective: To measure and compare mortality outcomes between dually eligible veterans transported by ambulance to a Veterans Affairs hospital and those transported to a non-Veterans Affairs hospital. Design: Retrospective cohort study using data from medical charts and administrative files. Setting: Emergency visits by ambulance to 140 Veteran Affairs and 2622 non-Veteran Affairs hospitals across 46 US states and the District of Columbia in 2001-18. Participants: National cohort of 583 248 veterans (aged ≥65 years) enrolled in both the Veterans Health Administration and Medicare programs, who resided within 20 miles of at least one Veterans Affairs hospital and at least one non-Veterans Affairs hospital, in areas where ambulances regularly transported patients to both types of hospitals. Intervention: Emergency treatment at a Veterans Affairs hospital. Main outcome measure: Deaths in the 30 day period after the ambulance ride. Linear probability models of mortality were used, with adjustment for patients' demographic characteristics, residential zip codes, comorbid conditions, and other variables. Results: Of 1 470 157 ambulance rides, 231 611 (15.8%) went to Veterans Affairs hospitals and 1 238 546 (84.2%) went to non-Veterans Affairs hospitals. The adjusted mortality rate at 30 days was 20.1% lower among patients taken to Veterans Affairs hospitals than among patients taken to non-Veterans Affairs hospitals (9.32 deaths per 100 patients (95% confidence interval 9.15 to 9.50) v 11.67 (11.58 to 11.76)). The mortality advantage associated with Veterans Affairs hospitals was particularly large for patients who were black (−25.8%), were Hispanic (−22.7%), and had received care at the same hospital in the previous year. Conclusions: These findings indicate that within a month of being treated with emergency care at Veterans Affairs hospitals, dually eligible veterans had substantially lower risk of death than those treated at non-Veterans Affairs hospitals. The nature of this mortality advantage warrants further investigation, as does its generalizability to other types of patients and care. Nonetheless, the finding is relevant to assessments of the merit of policies that encourage private healthcare alternatives for veterans.